Uniwersytet - rozwój - kultura - Kościelniak, Cezary (Wydawnictwo Naukowe UAM, 2015)
The book University, Development, Culture compares the differences of higher education policy between two types of the development of the states: the Western welfare state, and the state after the transformation, so called, posttransformation state. The main plot of the book is focused on the two cases: Switzerland and Poland. Author analyses the features of the development of given types of the development, including culture, as a one of the crucial factor of social progress. Considerations allow explaining the role of higher education policy in the development reforms and its cultural background. In the comparative case study of the higher education system in Poland and Switzerland, the following issues are taken to consider, like the processes of internationalization, demography, and link between academy and labor market. At the end author shows the idea of “sustainable university”, as a new model of higher education institution common to both types of the developments of the state.

Książka charakteryzuje przemiany w szkolnictwie wyższym w kontekście rozwoju państwa dobrobytu oraz państw posttransformacyjnych poprzez analizę teoretyczną oraz studia przypadków. Autor podejmuje zagadnienia: w jaki sposób kryzys państwa dobrobytu wpływa na politykę szkolnictwa wyższego? Na czym polega kulturowy wpływ uniwersytetu w rozwoju społecznym i ekonomicznym. Wreszcie, w jakich relacjach pozostaje uniwersytet w kontekście zrównoważonego rozwoju? Prowadzone w książce rozważania łączą perspektywę kulturową z instytucjonalną, dając tym samym szersze pole teoretyczne refleksji o obecnej kondycji uniwersytetu.
University, Development, Culture
Książka charakteryzuje przemiany w szkolnictwie wyższym w kontekście rozwoju państwa dobrobytu oraz państw posttransformacyjnych poprzez analizę teoretyczną oraz studia przypadków. Autor podejmuje zagadnienia: w jaki sposób kryzys państwa dobrobytu wpływa na politykę szkolnictwa wyższego? Na czym polega kulturowy wpływ uniwersytetu w rozwoju społecznym i ekonomicznym. Wreszcie, w jakich relacjach pozostaje uniwersytet w kontekście zrównoważonego rozwoju? Prowadzone w książce rozważania łączą perspektywę kulturową z instytucjonalną, dając tym samym szersze pole teoretyczne refleksji o obecnej kondycji uniwersytetu.
Keywords: uniwersytet; kultura; państwo dobrobytu; transformacja; rozwój